2013
DOI: 10.1007/s10142-013-0355-y
|View full text |Cite
|
Sign up to set email alerts
|

The substantive equivalence of transgenic (Bt and Chi) and non-transgenic cotton based on metabolite profiles

Abstract: Compositional studies comparing transgenic with non-transgenic counterpart plants are almost universally required by governmental regulatory bodies. In the present study, two T(2) transgenic cotton lines containing chitinase (Line 11/57) and Bt lines (Line 61) were compared with non-transgenic counterpart. To do this, biochemical characteristics of leaves and seeds, including amino acids, fatty acids, carbohydrates, anions, and cations contents of the studied lines were analyzed using GC/MS, high-performance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…However, in this study, we did not detect the intended protein, which was possibly due to both the low expression of the target gene and the limited accumulation of the target protein in PT leaves. In fact, in previous studies, the target protein was not detected at all (Zolla et al, 2008 ; Gong et al, 2012 ; Modirroosta et al, 2014 ). We had measured the Bt toxin protein content only 0.31 pg/g in cotton leaves by ELISA (Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, in this study, we did not detect the intended protein, which was possibly due to both the low expression of the target gene and the limited accumulation of the target protein in PT leaves. In fact, in previous studies, the target protein was not detected at all (Zolla et al, 2008 ; Gong et al, 2012 ; Modirroosta et al, 2014 ). We had measured the Bt toxin protein content only 0.31 pg/g in cotton leaves by ELISA (Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 85%
“…In fact, such unintended effects are not unique to GM plants, they are also widely observed during conventional plant breeding (Ladics et al, 2015 ). GMCs do not show greatly altered proteomes compared with their natural genetic variats or with species obtained through conventional genetic breeding (Modirroosta et al, 2014 ; Vidal et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic variations between the transgenic plant and its non-transgenic line might be due to the position effect of gene insertion [ 32 ]. According to the KEGG analysis, the present results revealed that DEPs between WT and BT lines mainly involved in photosynthetic organisms to take part into carbon fixation, photosynthesis, glyoxylate and dicarboxylate, oxidative phosphorylation, pentose phosphate pathway, and so on (Additional files 4 and 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The global cultivated area of GM cotton was reaching 23.9 million hectares in 2013. Previous studies mainly focused on detecting the biochemical compounds differences between transgenic and non-transgenic cotton, including amino acids fatty acids, carbohydrate content [ 32 ]. Fourier transform infrared spectroscopy (FTIR) was also used to detect the chemical and conformational changes between transgenic cotton seeds and their non-transgenic counterparts, and found both the indigenous and exogenous proteins structural changes in genetically modified organism (GMO) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the fungal stability index was increased with the increasing concentration of root exudates of transgenic cotton, indicating the fungal population and community in the soil was not affected by the much higher concentration of root exudates of transgenic cotton. http 1,2,3,4,5,6,7,8 …”
Section: Figure 4 Effect Of Root Exudates From Transgenic and Nont-tmentioning
confidence: 99%